Clinical evaluation and classification of patients with temporomandibular disorders using 'Diagnostic Criteria for Temporomandibular Disorders' - Cansu Alpaslan; Deniz Yaman (Gazi University, 2020)
Objective: The aim of the study was to evaluate the frequency of subgroups in a clinical setting of the patients with temporomandibular disorders (TMD) using 'Diagnostic Criteria for Temporomandibular Disorders (DC/TMD)'. Materials and Method: A total of 128 patients with TMD (92 females and 36 males, mean age 33.5 ± 8.28) were involved in the study. DC/TMD Axis I diagnosis criteria was used for the clinical examination of pain disorders and temporomandibular joint (TMJ) disorders. Also, in DC/TMD Axis I, The TMD Pain Screener, focusing on pain within the last 30 days, was used. In DC/TMD Axis II evaluation, the Jaw Functional Limitation Scale-8 (JFLS-8) was preferred to detect symptom severity and functional limitations. The data analysis was conducted by using the Chi-square, Kruskal Wallis test, and the Bonferroni correction for the Mann-Whitney U test. Results: Out of 128 patients, 120 patients (93.75%) had TMJ disorders that were accompanied by muscle pain disorders. The effect of gender and age on TMJ/muscle pain disorders was not significant (TMJ disorders; p=0.123, p=0.263; Muscle pain disorders; p=0.145, p=0.100, respectively). According to JFLS-8, the limitation in mastication (item 1 and 2) and joint mobility (item 4) were major complaints in the group of patients with 'disc displacement without reduction with limited opening' compared to the other TMJ disorders (p=0.001, p=0.004, p=0.007, p<0.008). Conclusion: DC/TMD Axis I is a significant reference to clinicians in the diagnosis and evaluation of TMD. In DC/TMD Axis II, JFLS-8 is an efficient instrument for the measurement of functional limitation associated with temporomandibular disorders.